Morphological Measurements and Anatomical Variations of The Clivus Bone Using Computed Tomography in Adults, Benghazi - makhlouf, Fatma; Karwad, Mustafa; Salem Algezeri (AlQalam Journal of Medical and Applied Sciences, 2025)
The clivus is the central part of the skull base that extends from the anterior part of the foramen magnum to the dorsum sellae. This study aimed to assess the morphological measurements including clivus length, width, and the anatomical variations of the clivus, including fossa navicularis magna (FNM), canalis basalis medianus (CBM), and clivus pneumatization, on computed tomography (CT) images. A total of 152 brain and cervical CT scans (96 males and 56 females), were retrospectively evaluated, the cases were over 18 years of age and randomly selected from the CT suit of the Radiology department at Aljalaa Hospital for Surgery and Accidents / Benghazi in duration from April 2017 to July 2018. The measurements of clivus width and length were assessed, in addition to the presence or absence of anatomical variants like fossa navicularis magna, canalis basilaris medianus, and clivus pneumatization. Data were analyzed through one-way ANOVA and T-test. The mean length and width of clivus were significantly longer in males (46.10 mm), (34 mm), than in females (44.9 mm), (33.73 mm) respectively (P<0.001). In the present study, regarding the anatomical variants Fossa Navicularis Magna was noted in (1.3%) cases, Canalis Basalis Medianus in (5.3 %) cases, and (1.3%) cases had incomplete pneumatization. Knowing the measurements of the clivus bone and the anatomical variations is important for radiologists and ENT surgeons for proper diagnosis and a safe and successful clival surgery. المنحدر هو الجزء المركزي من قاعدة الجمجمة، ويمتد من الجزء الأمامي للثقبة الكبرى إلى ظهر السرج. هدفت هذه الدراسة إلى تقييم القياسات المورفولوجية، بما في ذلك طول المنحدر وعرضه، والاختلافات التشريحية فيه، بما في ذلك الحفرة الزورقية الكبرى والقناة القاعدية الوسطى ، وتهوية المنحدر، باستخدام صور التصوير المقطعي المحوسب (CT). تم تقييم ما مجموعه 152 فحصًا مقطعيًا محوسبًا للدماغ والعنق (96 ذكرًا و56 أنثى) بأثر رجعي، وكانت الحالات فوق سن 18 عامًا وتم اختيارها عشوائيًا من بدلة الأشعة المقطعية بقسم الأشعة في مستشفى الجلاء للجراحة والحوادث / بنغازي في الفترة من أبريل 2017 إلى يوليو 2018. تم تقييم قياسات عرض وطول المنحدر، بالإضافة إلى وجود أو عدم وجود متغيرات تشريحية مثل الحفرة الزورقية الكبرى والقناة القاعدية الوسطى وتهوية المنحدر. تم تحليل البيانات من خلال تحليل التباين أحادي الاتجاه واختبار T. كان متوسط ​​طول وعرض المنحدر أطول بشكل ملحوظ في الذكور (46.10 مم) و (34 مم) منه في الإناث (44.9 مم) و (33.73 مم) على التوالي (P <0.001). في هذه الدراسة، وفيما يتعلق بالمتغيرات التشريحية، لوحظ وجود الحفرة الزورقية الكبرى (Fossa Navicularis Magna) في (1.3%) من الحالات، والقناة القاعدية الوسطى (Canalis Basalis Medianus) في (5.3%)، ووجود تهوية غير مكتملة في (1.3%) من الحالات. تُعدّ معرفة قياسات عظمة الجرف (Clivus) والاختلافات التشريحية أمرًا بالغ الأهمية لأطباء الأشعة وجراحي الأنف والأذن والحنجرة لضمان التشخيص الدقيق وإجراء جراحة جرف آمنة وناجحة